2018
DOI: 10.1038/s41467-018-04564-3
|View full text |Cite
|
Sign up to set email alerts
|

Vms1p is a release factor for the ribosome-associated quality control complex

Abstract: Eukaryotic cells employ the ribosome-associated quality control complex (RQC) to maintain homeostasis despite defects that cause ribosomes to stall. The RQC comprises the E3 ubiquitin ligase Ltn1p, the ATPase Cdc48p, Rqc1p, and Rqc2p. Upon ribosome stalling and splitting, the RQC assembles on the 60S species containing unreleased peptidyl-tRNA (60S:peptidyl–tRNA). Ltn1p and Rqc1p facilitate ubiquitination of the incomplete nascent chain, marking it for degradation. Rqc2p stabilizes Ltn1p on the 60S and recruit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 36 publications
(61 reference statements)
2
73
0
Order By: Relevance
“…Is there a dedicated termination factor that mediates release of the tagged nascent polypeptide chain in bacteria, analogous to Vms1/ANKZF1 in eukaryotes? (Kuroha et al, 2018;Su et al, 2019;Verma et al, 2018;Yip et al, 2019;Zurita Rendon et al, 2018). In summary, we demonstrate the involvement of YabO in RqcH-mediated bacterial RQC, and propose an alternative model for protein synthesis on the ribosome that utilizes binding and rebinding of two non-GTPase protein factors to execute a whole elongation cycle without the small ribosomal subunit or mRNA.…”
Section: Discussionmentioning
confidence: 71%
“…Is there a dedicated termination factor that mediates release of the tagged nascent polypeptide chain in bacteria, analogous to Vms1/ANKZF1 in eukaryotes? (Kuroha et al, 2018;Su et al, 2019;Verma et al, 2018;Yip et al, 2019;Zurita Rendon et al, 2018). In summary, we demonstrate the involvement of YabO in RqcH-mediated bacterial RQC, and propose an alternative model for protein synthesis on the ribosome that utilizes binding and rebinding of two non-GTPase protein factors to execute a whole elongation cycle without the small ribosomal subunit or mRNA.…”
Section: Discussionmentioning
confidence: 71%
“…This role of Vms1 corroborates well with the observed growth phenotype aggravation of MM-PMD-vms1Δ cells during stress ( Figure 6C). been recently shown to harbour peptidyl-tRNA hydrolase/endonuclease activity in its VLRF1 domain 15,25,35 , we speculate that these activities of the protein is important for suspending the mitochondrial respiration as an adaptive response to matrix stress.…”
Section: Sub-compartment Specific Stress Response Modulators Of Mitocmentioning
confidence: 80%
“…Interestingly, a substantial number of genes involved in cytosolic quality control like ssa1, ssa2, ssa4, hsp82, hsc82, ydj1, djp1, sis1, cct2 were found to be upregulated specifically in matrix stress ( Figure 3B). Importantly, component of Ribosome Quality Control (RQC), vms1, which is known to act as a peptidyl-tRNA endonuclease and protect mitochondria by antagonising the CAT-tailing activity of rqc2 15,25 was found to be specifically upregulated in matrix stress ( Figure 3B Figure S3A). Interestingly mdj1Δ did not aggravate the growth phenotype further while ecm10Δ (matrix hsp70) exhibited alleviation of growth phenotypes in both IMS and MM-PMD strains ( Figure S3A).…”
Section: Mitochondrial Ims and Matrix Responds Differently To Similarmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies revealed that Vms1 binds to ribosomes and the RQC complex, suggesting a role of RQC in mitochondrial quality control and a general function of Vms1 in RQC (Izawa et al, 2017). Indeed, Vms1 and its human homologue ANKZF1 have then been identified as peptidyl-tRNA hydrolase, required to remove the bound tRNA from the nascent chain, thereby facilitating release from the ribosome (Zurita Rendón et al, 2018;Verma et al, 2018).…”
Section: Rqcmentioning
confidence: 99%